Postglacial rebound and fault instability in Fennoscandia - Wu, Patrick P; Johnston, Paul; Lambeck, Kurt (Geophysical Journal International)
The best available rebound model is used to investigate the role that postglacial rebound plays in triggering seismicity in Fennoscandia. The salient features of the model include tectonic stress due to spreading at the North Atlantic Ridge, overburden pressure, gravitationally self-consistent ocean loading, and the realistic deglaciation history and compressible earth model which best fits the sea-level and ice data in Fennoscandia. The model predicts the spatio-temporal evolution of the state of stress, the magnitude of fault instability, the timing of the onset of this instability, and the mode of failure of lateglacial and postglacial seismicity. The consistency of the predictions with the observations suggests that postglacial rebound is probably the cause of the large postglacial thrust faults observed in Fennoscandia. The model also predicts a uniform stress field and instability in central Fennoscandia for the present, with thrust faulting as the predicted mode of failure. However, the lack of spatial correlation of the present seismicity with the region of uplift, and the existence of strike-slip and normal modes of current seismicity are inconsistent with this model. Further unmodelled factors such as the presence of high-angle faults in the central region of uplift along the Baltic coast would be required in order to explain the pattern of seismicity today in terms of postglacial rebound stress. The sensitivity of the model predictions to the effects of compressibility, tectonic stress, viscosity and ice model is also investigated. For sites outside the ice margin, it is found that the mode of failure is sensitive to the presence of tectonic stress and that the onset timing is also dependent on compressibility. For sites within the ice margin, the effect of Earth rheology is shown to be small. However, ice load history is shown to have larger effects on the onset time of earthquakes and the magnitude of fault instability.